Permeability and moisture distribution in oil palm wood and influence on development of effective method for veneer moisture reduction - Choo, Adrian Cheng Yong (2012)
In Malaysia, it is estimated that there is an excess of 14 million cubic meters of oil palm stem available every year due to replanting. However, the large variation in density and moisture content (MC) hinders a full utilization of the oil palm wood. In this study, an investigation was conducted to determine the basic properties of the oil palm wood and also the veneers that are derived from it. Permeability studies were also conducted on the palm wood and its influence on moisture was examined. A method was developed to reduce the moisture content of oil palm veneers before they were subjected to drying. Oil palm trees were selected randomly from the species Elaeies guineensis Jacq from Taman Pertanian Universiti located in Universiti Putra Malaysia, Serdang, Malaysia. The water and gas permeability values were measured using two specific apparatus that was set-up for the purpose of this study. The oil palm wood was segregated to outer middle and inner sections and samples of different lengths were tested. Anatomical studies were then carried out using an image analyzer to determine the maximum or theoretical permeability. Veneers obtained from a plywood factory in Kedah were examined for density and moisture content variations and its distribution throughout the length of the stem. A specially designed and built machine (Malaysian Patent No: MY-143318-A) was used to conduct a pre-drying process on green veneers and optimization of pressing conditions on reducing the moisture content was carried out using the Response Surface Method (RSM). The permeability results showed that the oil palm wood is more permeable when it is green compared to after it is dried. Shorter samples had a higher permeability value compared to longer samples. Results showed that the different sections influenced both the water and gas permeability values of the oil palm wood with the middle section giving the highest values followed by the inner and outer sections respectively. The maximum or theoretical permeability was consistently higher than the water and gas permeability for all samples. The average permeability values for 5 cm samples were 23.29 darcies, 5.91 darcies and 0.96 darcies for the maximum or theoretical, water and gas respectively. The density of the oil palm veneers decreases as the veneers were peeled towards the inner section of the stem while the inverse was true for MC. The outer veneers had an average density of 0.337 g/cm3 compared to 0.272 g/cm3 for the inner veneers. The veneers obtained from the top part of the stem had higher density values (0.318 g/cm3) compared to veneers obtained from the bottom part of the stem (0.290 g/cm3). The inner veneers had an average MC of 313.4 % while the outer veneers had an average MC of 229.0 %. There was not a significant difference in MC between veneers taken from the bottom and top part of the stems. Optimum conditions were obtained in the pre-drying process. They were feeding for two passes, 82 kgf/cm2 pressure and 41.49 Hz roller speed for outer veneers and two passes, 77 kgf/cm2 pressure and 41.49 Hz roller speed for inner veneers. The expected response was 17.62 % and 22.01 % MC reduction for outer and inner veneers respectively. This study found that the different sections of the oil palm stem showed different physical properties. The study suggests that the oil palm wood or veneers should be segregated to outer and inner sections to maximize efficiency and to improve homogeneity in various processes concerning it. The method of reducing moisture content was proven to be successful and it can be utilized before the drying process to lower drying time and cost.